(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Parasites attack fish causing destruction of skin and gill epithelium and injury to tissues or organs in the process of burrowing or consuming food. The gastrointestinal parasites of Clarias gariepinu (Catfish) from River Nasarawa were investigated in this study. Two hundred (200) samples of Clarias gariepinus of different sizes and sexes were obtained fresh and brought to Zoology laboratory, Nasarawa State University, Keffi for intestinal parasites examination. The fish were dissected through the abdomen by making a longitudinal slit on the ventral surface from the point of pectoral fins to the anus using a blade. The gastrointestinal tract was sectioned into oesophagus, stomach and intestine. The contents of various parts of the gastrointestinal tract were examined for parasites using floatation and sedimentation methods. Sixty (60) out of 200, that is 30% fish samples examined were found to be infected with parasites. A total of 74 parasites were isolated from different parts of gastrointestinal tract belonging to five (5) species. 3(3.33%) parasites of Proamallanus spp were isolated from oesophagus, 45(60.00%) parasites of Hexamita spp, 10(13.33%) parasites of Protoopalina spp and 12(18.34%) parasites of Microsporidian spp were isolated from stomach while 4(5.00%) parasites of D. latum were isolated from the intestine. Parasitic infection presents a potential threat to the health of fish and as a result of this, an understanding of the intestinal parasites of fish in the wild is important in order to find ways of avoiding mortality and disease.